Development of a high energy density gas diffusion electrode for Li-O2 batteries - Jenkins, M (2023)
The lithium-oxygen (Li-O2) battery has the highest theoretical specific energy and energy density amongst modern energy storage technologies. If these can be realised in a practical device, the Li-O2 battery could transform energy storage. There are, however, significant challenges which must be overcome before the move towards a practical device can be considered. These include the improvement of the reversibility of the positive electrode reactions, the development of a high-performance positive Gas Diffusion Electrode (GDE) and the stabilisation of the Li metal negative electrode. The following thesis deals with the second of these challenges, namely the development of a GDE which allows for sufficient O2 mass transport to achieve high areal capacities at practical discharge rates.